An updated analysis of hominin phylogeny with an emphasis on re-evaluating the phylogenetic relationships of Australopithecus sediba. Issue 175 (February 2023) - Mongle, Carrie S.; Strait, David S.; Grine, Frederick E.
Abstract: The discovery and description of Australopithecus sediba has reignited the debate over the evolutionary history of the australopiths and the genus Homo . It has been suggested that A. sediba may be an ancestor of Homo because it possesses a mosaic of derived Homo -like and primitive australopith-like traits. However, an alternative hypothesis proposes that the majority of the purported Homo -like craniodental characters can be attributed to the juvenile status of the type specimen, MH1. We conducted an independent character assessment of the craniodental morphology of A. sediba, with particular emphasis on evaluating whether the ontogenetic status of MH1 may have affected its purported Homo -like characteristics. In doing so, we have also expanded fossil hypodigms to incorporate the new Australopithecus anamensis cranium from Woranso-Mille (MRD-VP-1/1), as well as recently described Paranthropus robustus cranial remains from Drimolen (DNH 7, DNH 155). Morphological character data were analyzed using both standard parsimony and Bayesian techniques. In addition, we conducted a series of Bayesian analyses constrained to evaluate the hypothesis that Australopithecus africanus and A. sediba are sister taxa. Based on the results of the parsimony and Bayesian analyses, we could not reject the hypothesis that A. sediba shares its closest phylogenetic affinities with the genus Homo . Therefore, based on currently available craniodental evidence, we conclude that A. sediba is plausibly the terminal end of a lineage that shared a common ancestor with the earliest representatives of Homo . We caution, however, that the discovery of new A. sediba fossils preserving adult cranial morphology or the inclusion of postcranial characters may ultimately necessitate a re-evaluation of this hypothesis.